2020
DOI: 10.1038/s41467-020-16465-5
|View full text |Cite
|
Sign up to set email alerts
|

Continuously controllable photoconductance in freestanding BiFeO3 by the macroscopic flexoelectric effect

Abstract: Flexoelectricity induced by the strain gradient is attracting much attention due to its potential applications in electronic devices. Here, by combining a tunable flexoelectric effect and the ferroelectric photovoltaic effect, we demonstrate the continuous tunability of photoconductance in BiFeO3 films. The BiFeO3 film epitaxially grown on SrTiO3 is transferred to a flexible substrate by dissolving a sacrificing layer. The tunable flexoelectricity is achieved by bending the flexible substrate which induces a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 37 publications
2
98
0
Order By: Relevance
“…The enhancement of E b can be explained by the fact that a depolarization electric field at the 2–2 type interfaces between BTO layers and PVDF layers inhibits the mobile charges across interfaces, which is confirmed by phase‐field simulations. In future cases, the preparation process is also applicable to develop a series of 2–2 type composites interlayered by single‐crystal perovskite films, such as SrTiO 3 , [ 64 ] BiFeO 3 , [ 65 ] etc. This kind of composite can further enhance the U further and may be applied in electronics and electrical power systems.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of E b can be explained by the fact that a depolarization electric field at the 2–2 type interfaces between BTO layers and PVDF layers inhibits the mobile charges across interfaces, which is confirmed by phase‐field simulations. In future cases, the preparation process is also applicable to develop a series of 2–2 type composites interlayered by single‐crystal perovskite films, such as SrTiO 3 , [ 64 ] BiFeO 3 , [ 65 ] etc. This kind of composite can further enhance the U further and may be applied in electronics and electrical power systems.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chu et al [21] observed a significant strain gradient-induced enhancement of photocurrent at the morphotropic phase boundaries (MPBs) in mixed-phase BiFeO 3 (BFO) films. In addition, Guo et al [22] demonstrated the Flexoelectricity has become an emerging tool to tailor the material properties. The flexoelectric modulation of ferroelectric photovoltaic (FEPV) properties is of particular interest, because it offers an opportunity to boost the photovoltaic efficiency.…”
Section: Significant Modulation Of Ferroelectric Photovoltaic Behavior By a Giant Macroscopic Flexoelectric Effect Induced By Strain-relamentioning
confidence: 99%
“…In contrast, flexoelectricity, the coupling between an electric polarization and strain gradient, [ 11 , 12 , 13 , 14 , 15 ] has been demonstrated in recent studies on various material systems to modulate physical properties, for example, a photovoltaic effect, Schottky barrier, resistance, or polarization, has been reported in BiFeO 3 , [ 16 ] halide perovskite, [ 17 ] Si, [ 18 ] TiO 2 , [ 18 , 19 ] and (Nb‐)SrTiO 3 , [ 14 , 15 , 18 , 19 ] to name a few. Basically, flexoelectricity is a universal property of all dielectric materials including centrosymmetric materials, which occurs under an inhomogeneous strain field.…”
Section: Introductionmentioning
confidence: 99%